Ageing in India: socio economic and health dimensions - Alam, Moneer (New Delhi, 2006)
The socioeconomic, health, and public-policy aspects of ageing in India are presented in this study that draws on empirical research to assess the country$1 (Bs preparedness. The study argues that many of the fundamental issues that need to be addressed by a country with a large ageing population are not fully understood by public agencies.s
Keywords: Fertility-Marality transition; Older people--Economic conditions